(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Spondylolisthesis is forward slipping of upper vertebra in relations to its lower one, commonest is L4-L5. The ideal surgical treatment of spondylolisthesis is still controversial. Posterior lumber interbody fusion with pedicle fixation is one of treatment choices for the lumber spondylolisthesis. Forty patients who operated through posterior lumber interbody fusion and pedicle screw fixation by single surgeon was included from January 2012 to March 2015. Periodical follow-up was done both clinically and radiologically up to 6 months. Patient outcome was completed based on pain relief graphic rating scale and Oswestry disability index. In our series, the excellent outcome were 25 patients (62.5%), good were 12 patients (30%), and fair were 3 patients (7.5%). There were no poor outcome and no new neurological deficit. This study concludes that posterior lumber inter-body fusion with pedicle is an effective treatment for the lumber spondylolisthesis. It helps to maintain the biomechanics, associated with less complication and improve the quality of life of patient.